SURGICAL EXCISION OF TRANSMISSIBLE VENEREAL TUMOR FOLLOWED BY VINCRISTINE SULFATE CHEMOTHERAPY IN A MALE LOCAL DOG - Stephanie Levina; I Wayan Gorda; I Gusti Agung Gde Putra Pemayun (Buletin Veteriner Udayana, 2025)
Transmissible venereal tumor (TVT) is a malignant tumor that commonly occurs in dogs. It can be transmitted through mating, licking, or sniffing tumor lesions. The purpose of this study was to describe the successful treatment of TVT by surgical excision followed by vincristine sulfate chemotherapy. A 7-year-old local male dog weighing 14 kg presented with a penile mass accompanied by bloody discharge. Histopathological examination revealed a population of tumor cells consisting of lymphoblast-like cells with a homogeneous polyhedral shape. The tumor cells were separated by stroma and exhibited moderate mitotic figures. Treatment consisted of surgical excision of the tumor mass followed by vincristine sulfate chemotherapy at a dose of 0.025 mg/kg administered intravenously three times at one-week intervals. Postoperatively, long-acting amoxicillin was administered as an antibiotic at a dose of 15 mg/kg body weight (BW) intramuscularly every 48 hours on days 0, 2, and 4. For analgesia, meloxicam was administered at a dose of 0.2 mg/kg BW subcutaneously once daily for four days. A hematopoietic stimulant (hematodin) was administered at a dose of 1 mL/5 kg BW intramuscularly once daily for five days. On day 21, the dog showed signs of healing, indicated by dried wounds, disappearance of suture marks, and normalization of penile size, suggesting complete tumor removal. The combination of surgical excision and chemotherapy proved effective in treating TVT in dogs.